2021
DOI: 10.21037/apm-21-3626
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of telemedicine for cardiovascular disease management: systematic review and meta-analysis

Abstract: Background: With the development of information communication technology (ICT), telemedicine has become a promising option for patients with chronic diseases who need continuous monitoring at home or in remote health care facilities. As cardiovascular disease (CVD) is responsible for an estimated 17.9 million deaths globally each year, it is appropriate to evaluate the effectiveness of telemedicine for the health care management of CVD patients. Methods:The Library of Congress, LISTA (EBSCO), PubMed (NLM), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…We discovered no statistical significance for BMI, LDL cholesterol, systolic, and diastolic blood pressure at the meta-analysis level. This result did not agree with those of previous related studies,43 44 probably because the patients’ enrollment criterion was T2DM and most of the interventions focused on reducing HbA1c with much less attention on BMI, LDL-cholesterol, systolic and diastolic blood pressure, thereby resulting in poor intervention effects. Studies included in this systematic review employed more than five questionnaires for the secondary outcomes, although sometimes the same uniform questionnaire was used.…”
Section: Discussioncontrasting
confidence: 81%
“…We discovered no statistical significance for BMI, LDL cholesterol, systolic, and diastolic blood pressure at the meta-analysis level. This result did not agree with those of previous related studies,43 44 probably because the patients’ enrollment criterion was T2DM and most of the interventions focused on reducing HbA1c with much less attention on BMI, LDL-cholesterol, systolic and diastolic blood pressure, thereby resulting in poor intervention effects. Studies included in this systematic review employed more than five questionnaires for the secondary outcomes, although sometimes the same uniform questionnaire was used.…”
Section: Discussioncontrasting
confidence: 81%
“… 62 One systematic review and meta-analysis has suggested a trend towards improved EQ-5D quality of life scores among telemedicine users compared with usual care, but there are only a few small studies in this area. 63 There is broader concern about replacing relationship-based clinical care with telemedicine-guided algorithmic pathways, which might not improve care for some patients. New care pathways must ensure additional support for groups at risk of digital exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…62 One systematic review and metaanalysis has suggested a trend towards improved EQ-5D quality of life scores among telemedicine users compared with usual care, but there are only a few small studies in this area. 63 There is broader concern about replacing relationship-based clinical care with telemedicine-guided algorithmic pathways, which might not improve care for some patients. New care pathways must ensure additional support for groups at risk of digital exclusion.…”
Section: Favours Intervention Favours Controlmentioning
confidence: 99%